2020
DOI: 10.1140/epjp/s13360-020-00543-0
|View full text |Cite
|
Sign up to set email alerts
|

A new self-consistent approach of quantum turbulence in superfluid helium

Abstract: We present the Fully cOUpled loCAl model of sUperfLuid Turbulence (FOU-CAULT) that describes the dynamics of finite temperature superfluids. The superfluid component is described by the vortex filament method while the normal fluid is governed by a modified Navier-Stokes equation. The superfluid vortex lines and normal fluid components are fully coupled in a self-consistent manner by the friction force, which induces local disturbances in the normal fluid in the vicinity of vortex lines. The main focus of this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 92 publications
1
41
0
Order By: Relevance
“…Microscopically, this assumption does not hold. Recent studies [31][32][33][34] have shown that the normal fluid profile is nontrivially modulated by the presence of quantized vortices, through mutual friction on the scale of the intervortex distance. However, in the analysis below, we consider only the macroscopic vortex bundle structure that develops in the macroscopic steady normal flow; a study of the characteristic small-scale structures that emerge due to coupled dynamics remains future work to be dealt with.…”
Section: Bundle Formation In Region IImentioning
confidence: 99%
“…Microscopically, this assumption does not hold. Recent studies [31][32][33][34] have shown that the normal fluid profile is nontrivially modulated by the presence of quantized vortices, through mutual friction on the scale of the intervortex distance. However, in the analysis below, we consider only the macroscopic vortex bundle structure that develops in the macroscopic steady normal flow; a study of the characteristic small-scale structures that emerge due to coupled dynamics remains future work to be dealt with.…”
Section: Bundle Formation In Region IImentioning
confidence: 99%
“…The relation (20) produces three (and only three) differential equations that provide a closure to the system. Too see this, let us insert (20) into the first equation in (14), which gives a condition of the type…”
Section: Closure Of the Macroscopic Model: The Dynamics Of Vorticesmentioning
confidence: 99%
“…and provide a closure to the system. In fact, a delicate point in the construction of a model for macroscopic superfluid hydrodynamics is the derivation from microphysics of a prescription for (20), which may be extracted from simulations of the average velocity of an ensemble of vortex lines (see e.g., [20] for 4 He case, or [14] for a neutron star application). This should be done by solving a "force balance equation" for every vortex in a fluid element (i.e., by requiring that the forces acting on the single vortices vanish [6,7,9]), as will be further discussed in Section 3.…”
Section: Closure Of the Macroscopic Model: The Dynamics Of Vorticesmentioning
confidence: 99%
See 2 more Smart Citations